LEARNING MANAGEMENT SYSTEM IN HIGHER EDUCATION: AN EXPERIENCE AT MELBOURNE UNIVERSITY - Kasinyo Harto (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
Learning pattern of Islamic higher education, especially in Indonesia, is generally dominated by conventional learning with teacher-centered approach in which learning process focuses on the lectures, not on the students. As a result, the students tend to be passive and poor of creativity, less capable of arguing, trying, and appreciating science. Considering this reality, it is a necessity to make some efforts of reconstructing that learning pattern. One of them is doing bench-marking against universities in Australia, like Melbourne University. Therefore, this study focuses on learning management system of Melbourne University in relation to the development of learning quality. The result of the study shows that learning strategy developed at Melbourne University enhances student active learning through a variety of learning experiences, such as on-line discussion (collaborative learning), weekly readings, weekly exams, weekly assignments (independent learning), class presentation, and round table discussion. In addition, learning management system at Melbourne University has been running well along with an integrated system of ICT that enables the lecturers to communicate their courses and enables the students to interact dynamically with the tasks, lectures, and other students. It is expected that this can be an inspiration and alternative model for Islamic higher education institutions in Indonesia in designing their learning pattern and environment to promote active learning.